2020
DOI: 10.12659/ajcr.927956
|View full text |Cite
|
Sign up to set email alerts
|

A 44-Year-Old Hispanic Man with Loss of Taste and Bilateral Facial Weakness Diagnosed with Guillain-Barré Syndrome and Bell’s Palsy Associated with SARS-CoV-2 Infection Treated with Intravenous Immunoglobulin

Abstract: Patient: Male, 44-year-old Final Diagnosis: COVID-19 • Guillain-Barré syndrome Symptoms: Facial paralysis Medication: — Clinical Procedure: — Specialty: Critical Care Medicine • Medicine, General and Internal • Neurology Objective: Rare disease Background: This case report is of a patient who presented with loss of taste and facial weakness and was diagnosed with Guillain-Barré… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 27 publications
3
36
0
2
Order By: Relevance
“…As is evident by the fact that 303/430 (70%) patients we identified had CSF SARS-CoV-2 PCR testing performed, it is feasible to perform PCR testing for SARS-CoV-2 in CSF [ [5] , [6] , [7] , [8] , [9] , [10] , 15 , 17 , 22 , 24 , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [68] , [69] , [70] , [71] , 73 , 74 , [76] , [77] , [78] , 81 , 84 , 88 , 89 , 95 , 97 , 98 , 101 , 103 , 105 , 108 , 109 , 111 , 113 , 116 , 119 , 122 , 123 , 125 ,…”
Section: Discussionmentioning
confidence: 99%
“…As is evident by the fact that 303/430 (70%) patients we identified had CSF SARS-CoV-2 PCR testing performed, it is feasible to perform PCR testing for SARS-CoV-2 in CSF [ [5] , [6] , [7] , [8] , [9] , [10] , 15 , 17 , 22 , 24 , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [68] , [69] , [70] , [71] , 73 , 74 , [76] , [77] , [78] , 81 , 84 , 88 , 89 , 95 , 97 , 98 , 101 , 103 , 105 , 108 , 109 , 111 , 113 , 116 , 119 , 122 , 123 , 125 ,…”
Section: Discussionmentioning
confidence: 99%
“…All patients experienced Bell’s Palsy during infection. Treatment ranged from antivirals and/or steroids or intravenous immunoglobulins [ [153] , [154] , [155] , [156] ].…”
Section: Sars-cov-2 Infection Of the Nervous Systemmentioning
confidence: 99%
“…Of 242 publications from December 1, 2019 and November 18, 2020 that described a unique patient diagnosed with COVID-19 via SARS-CoV-2 PCR or serology who had a neurological symptom and had CSF obtained, we identified 51 that met inclusion criteria. After review of the 51 publications, we identified 70 patients reported to have altered olfactory and/or gustatory function (anosmia/cacosmia/hyposmia and/or ageusia/dysgeusia/hypogeusia); 40 (57%) had both olfactory and gustatory dysfunction, 17 (24%) had isolated olfactory dysfunction and 13 (19%) had isolated gustatory dysfunction [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] . In addition to altered olfactory and/or gustatory function, 39 (56%) had symptoms that localized to the central nervous system and 31 (44%) had symptoms that localized to the peripheral nervous system.…”
Section: Resultsmentioning
confidence: 99%
“…In 13/66 (20%) patients, the CSF WBC count was 0 cells/µL or the CSF WBC:RBC ratio was <1:1,000. The majority of patients (38/66; 58%) had a CSF WBC count of 1-5 cells/µL or were noted to have “no pleocytosis” or “normal WBC.” [10] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [29] , [30] , [33] , [36] , [37] , [38] , [40] , [41] , [42] , [44] , [45] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] There were 11/66 (17%) patients who had a CSF WBC count >5 cells/µL or noted to be “increased.” [8] , [12] , [17] , [28] , [31] , [32] , [33] , [34] , [35] , [39] , [46]
Fig. 3 Cerebrospinal Fluid White Blood Cell Count Results.
…”
Section: Resultsmentioning
confidence: 99%